2017
DOI: 10.3389/fmicb.2017.02206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Forage to Concentrate Ratios on Dynamic Profile Changes and Interactions of Ruminal Microbiota and Metabolites in Holstein Heifers

Abstract: A better understanding of global ruminal microbiota and metabolites under extensive feeding conditions is a prerequisite for optimizing rumen function and improving ruminant feed efficiency. Furthermore, the gap between the information on the ruminal microbiota and metabolites needs to be bridged. The aim of this study was to investigate the effects of a wide range of forage to concentrate ratios (F:C) on changes and interactions of ruminal microbiota and metabolites. Four diets with different F:C (80:20, 60:4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
121
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 84 publications
(139 reference statements)
37
121
2
2
Order By: Relevance
“…In the current study, Entodinium was the predominate protozoa genus in the rumen, which was consistent with previous studies [6,77,78]. Entodinium has been characterized as a starch feeder.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, Entodinium was the predominate protozoa genus in the rumen, which was consistent with previous studies [6,77,78]. Entodinium has been characterized as a starch feeder.…”
Section: Discussionsupporting
confidence: 92%
“…Ruminal pH was monitored every 4 hours, and the acid infusion rate was varied by animal to achieve a ruminal pH between 6.0 and 6.1. When ruminal pH dropped below 6.0, the infusion rate was decreased by 10 ml/h, and the ruminal pH was rechecked in 30 to 60 minutes. The infusion rate was adjusted upwards if ruminal pH was above 6.1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal species diversity (Shannon) and richness (Chao 1) of bovine rumens (control, without CTs) were 0.245 and 152.2, respectively (Table 2): these value are lower than previous reports (Tuckwell et al 2005;Lee et al 2012;Zhang et al 2017) and are likely a consequences of the breeds of animals and feed that affect fungal population dynamics as well as effects of samplings and analytical procedures. Quantitative methods of evaluating the a-diversity (richness and species diversity) of rumen fungi communities indicated that inclusion of different MWs CT fraction showed significant interactions between treatments: higher-MW CT fractions, such as fractions F1 and F2 exhibited lower Chao1 index and Shannon index compared with lower-MW CT fractions (fractions F3, F4 and F5).…”
Section: Discussionmentioning
confidence: 67%
“…Among the technologies in metabolomics, gas chromatography with time-of-flight mass spectrometry (GC-TOF/MS) has been widely used due to the advantages of high resolution and sensitivity (Adebo et al, 2018;Ding et al, 2009;Salvatore, Gyong, Tobias, Cataldi, & Oliver, 2010;Sun et al, 2015;Tobias et al, 2009). With the help of the effective method, comprehensive and quantitative analysis of metabolites can be achieved, which can be used to characterize metabolic mechanism at molecular level (Zhang et al, 2017). However, the comprehensive research and optimization of the Douchi fermentation with GC-TOF/MS technology are rarely reported so far.…”
mentioning
confidence: 99%